Auditor Ethics: Do Experience and Gender Influence Auditors’ Moral Awareness? - Carrera, Nieves; Van der Kolk, Berend (Managerial Auditing Journal, 2020)
Purpose – The purpose of this paper is to examine how experience and gender relate to the auditors’ moral awareness. Design/methodology/approach– Hypotheses are informed by a neurocognitive approach of ethical decision-making and tested using survey data from 191 auditors of a Big Four audit firm in The Netherlands. Findings – The main findings indicate that more experienced auditors (i.e., those with more years of work experience, a higher rank, and older) show higher levels of moral awareness. This positive relationship is stronger for morally questionable situations related to accounting and auditing, compared to general business moral dilemmas. In addition, the results support the expectation that on average, female auditors have higher moral awareness than their male counterparts. Originality/value – To our knowledge, this is the first study that considers a neurocognitive approach to inform hypotheses about the antecedents of auditors’ moral awareness. The findings suggest that the involvement of experienced auditors in ethical decision-making processes may be beneficial given their enhanced ability to identify ethically disputable situations as such. Furthermore, increasing the number of females in senior positions may positively affect ethical decision-making in audit firms. Lastly, this paper presents directions for future research.
Keywords: Auditors; Ethical Decision Making; Moral Awareness; Experience; Gender; 71 Ética::7102 Ética de individuos::7102.02 Códigos de conducta ética; ODS 5 - Igualdad de género